A tree cognitive navigation system based on two-dimensional code and GPS. (2018) - Hu, Wenjie; Wang, Chunling; Mo, Qiaochu; Wang, Bo
The recognition of trees plays an important role in the construction of ecological civilisation. In order to strengthen tree information management and help the public to have a better understanding of trees, an Android-based tree cognitive navigation system for smart phones was developed. Using two-dimensional code and GPS technologies, the system can rapidly acquire geographic coordinates and species of trees. In this paper, the theory, system framework and key technologies of the system are presented. Subsequently, a tree cognitive system based on two-dimensional code and GPS was developed for Beijing Forestry University. The system implementation approach has broad application prospects. The case study showed that it is portable, practical, user-friendly, and network-independent and has good potential for application and expansion.